The Development of Religious Moderation in the Multicultural Community of Sindang Sari Village, Tanjung Bintang District, South Lampung Regency - Ruslan, Idrus; Irham, Muhammad Aqil; Salim, Luthfi (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
Multiculturalism is the nature of human life to live side by side, not in conflict. Sindang Sari Village is multicultural because it has various religions and ethnic groups. This potential needs to be managed by instilling valuesabout religious moderation. It does not have to wait for conflict to occur but needs to be done as early as possible as a preventive measure so that undesirable things do not happen. This service method is divided into two groups consisting of religious leaders, elder community leaders and youth leaders. Service provides pre-tests and post-tests to measure people’s understanding of religious moderation and tolerance. The results of the pre-test showed sufficient mutual respect without any social contact. After the service, the results of the post-test show a significant increase in understanding that religious moderation is not only done by respecting each other but by carrying out acts of mutual friendship, cooperation in cooperation, and mutual help.